Myocyte-specific enhancer factor 2 and thyroid hormone receptor associate and synergistically activate the alpha-cardiac myosin heavy-chain gene. - Lee, Y (1997)
The muscle-specific regulatory region of the alpha-cardiac myosin heavy-chain (MHC) gene contains the thyroid hormone response element (TRE) and two A/T-rich DNA sequences, designated A/T1 and A/T2, the putative myocyte-specific enhancer factor 2 (MEF2) binding sites. We investigated the roles of the TRE and MEF2 binding sites and the potential interaction between thyroid hormone receptor (TR) and MEF2 proteins regulating the alpha-MHC promoter. Deletion mutation analysis indicated that both the A/T2 motif and TRE were required for muscle-specific expression of the alpha-MHC gene. The alpha-MHC enhancer containing both the A/T2 motif and TRE was synergistically activated by coexpression of MEF2 and TR in nonmuscle cells, whereas neither factor by itself activated the alpha-MHC reporters. The reporter construct containing the A/T2 sequence and the TRE linked to a heterologous promoter also showed synergistic activation by coexpression of MEF2 and TR in nonmuscle cells. Moreover, protein binding assays demonstrated that MEF2 and TR specifically bound to one another in vitro and in vivo. The MADS domain of MEF2 and the DNA-binding domain of TR were necessary and sufficient to mediate their physical interaction. Our results suggest that the members of the MADS family (MEF2) and steroid receptor superfamily (TR) interact with one another to synergistically activate the alpha-cardiac MHC gene expression.